Exploring Strategies to Improve The Service Quality of Food in Community-Based Ecotourism: A Case Study of Trapeang Sangke Community-Based Ecotourism, Kampot Province - Noh Navey (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2022)
Trapeang Sangke Community-Based Ecotourism is a well-known community in Kampot province and also an attractive ecotourism area. TPSK CBET still faces some issues related to food service that require the CBET to further strengthen food services to meet the needs of tourists. As for the problems with the food service are lack of service providers, poor food hygiene, limited food quality standards, as well as hospitality of food service, including with a number of other issues. TPSK CBET is trying to address these issues as quickly as possible to improve the food service sector in order to attract more tourists and provide income for the CBET, especially local CBET as a whole. In the meantime, the research finds out the strategies to provide for improving the food service quality in Trapeang Sangke Community-Based Ecotourism. In addition, this research has four main questions such as: 1) What are quality and food service? 2) What are the tourists’ perception on the service quality of food? 3) What are the factors that influence service quality of food? 4) What are the strategies to provide for improving the service quality of food? Key words: Service quality, Food service quality, Food service improvement, CBET